Network pharmacology dissection of multiscale mechanisms of herbal medicines in stage IV gastric adenocarcinoma treatment. Issue 35 (August 2016) - Gao, Li; Hao, Jian; Niu, Yang-Yang; Tian, Miao; Yang, Xue; Zhu, Cui-Hong; Ding, Xiu-Li; Liu, Xiao-Hui; Zhang, Hao-Ran; Liu, Chang; Qin, Xue-Mei; Wu, Xiong-Zhi
Abstract : Abstract: Increasing evidence has shown that Chinese Herbal Medicine (CHM) has efficient therapeutic effects for advanced gastric adenocarcinoma, while the therapeutic mechanisms underlying this treatment remain unclear. In this study, the Kaplan–Meier method and Cox regression analysis were used to evaluate the survival benefit of CHM treatment, and correlation analysis was applied to identify the most effective components in the formulas. A network pharmacological approach was developed to decipher the potential therapeutic mechanisms of CHM. CHM treatment was an independent protective factor. The hazard ratio was 0.364 (95% CI 0.245–0.540; P  < 0.001). The median survival time was 18 months for patients who received CHM treatment, while for patients without CHM treatment was decreased to 9 months ( P  < 0.001). Thirteen out of the total 204 herbs were significantly correlated with favorable survival outcomes ( P  < 0.05), likely representing the most effective components in these formulas. Bioinformatics analyses suggested that the simultaneous manipulation of multiple targets in proliferation pathways (such as epidermal growth factor receptor, fibroblast growth factor receptor 2, human epidermal growth factor receptor 2, proliferating cell nuclear antigen, and insulin like growth factor 2) and the process of cancer metastasis (collagen families, fibronectin 1 and matrix metalloproteinases families) might largely account for the mechanisms of the 13 herbs against gastric adenocarcinoma. A network pharmacology method was introduced to decipher the underlying mechanisms of CHM, which provides a good foundation for herbal research based on clinical data. Abstract : Supplemental Digital Content is available in the text